(untitled) (Revista Apotheke, 2025)
The goal of this paper is to approach John Dewey’s concept of experience and its epistemological implications when it comes to the relations between theory and practice. With a distinction from notions from the British empiricism and from the Kantian transcendental system, the text explores through which ways the notion of Dewey’s “naturalist empiricism”, in proposing a resizing of the notion of what constitutes experience, allows comprehending it as something more profound than the mere sensitive perception of reality but a means of properly penetrating reality and relating to it. Thus, our thesis is that there is a gain also in the conception of what knowledge is, how it’s formed and how it interferes in experience. For empirical sciences as much as for philosophy, knowledge in Dewey is related to the glimpse of new meaning relations in experience and new possibilities of comprehension and action – thus the deeper relation amongst theory and practice.